Penerapan Model Pembelajaran Project Based Learning meningkatkan Profil Pelajar Pancasila Dimensi Gotong Royong Siswa di SMP Negeri 12 Ambon - Habel, Yulet; Habel, Lisa; Pipiana, Sentia; Kauy, Viladelviani; Tebiari, Since (PGRI Kota Semarang, 2025)
This study aims to improve the collaborative dimension of the Pancasila Student Profile through the implementation of the Project Based Learning (PjBL) model in Christian Religious Education at SMP Negeri 12 Ambon. This classroom action research was conducted in two cycles with 33 students of class VIII-3 as the subjects. Data were collected through observation, interviews, and documentation. The observed indicators included group communication, discussion participation, cooperation in project completion, and peer concern. The results show that in cycle I, 75.76% of students were still in the underdeveloped category. However, in cycle II, 75.75% of students reached the well-developed category. This indicates that the implementation of the PjBL model is effective in enhancing students' collaborative behavior Keywords: Project Based Learning, collaboration, Pancasila Student Profile, Christian Religious Education